Penggunaan Katalis SiO2/ZnO untuk Menghilangkan Pewarna Rhodamin B Secara Efisien melalui Impregnasi Basah - Luthfi, Muhamad; Afrizon, Imam Wahyudi (MASALIQ, 2024)
This study explores the removal of Rhodamine B dye from wastewater using SiO2/ZnO catalysts synthesized by wet impregnation with varying zinc nitrate loadings (0.25–1.25 g). The catalyst prepared with 1 g of Zn(NO₃)₂ exhibited the highest activity, achieving a remarkable 95% degradation of Rhodamine B under UV irradiation. This enhanced performance is attributed to optimized active site availability on the catalyst surface. FTIR characterization confirmed the presence of both SiO₂and ZnO, with characteristic vibrational modes observed at 1067.44 cm⁻¹ and 428.72 cm⁻¹, respectively. These findings highlight the promising potential of tailored SiO₂/ZnO catalysts for efficient and environmentally friendly treatment of dye-contaminated wastewater.